Effects of intake conditions and octane sensitivity on GCI combustion at early injection timings. (15th August 2021) - Pan, Jiaying; Li, Xianyu; Yin, Zenghui; Shu, Gequn; Liu, Changwen; Wei, Haiqiao
Highlights: Effect of intake conditions on GCI combustion was investigated with low-octane gasoline. Both low-temperature and high-temperature reactions affect GCI combustion processes. Pressure promotes low-temperature reaction and temperature/equivalence ratio suppresses it. High-temperature heat release is sensitive to octane sensitivity due to toluene blending. Cool flame appears in fuel-lean region while hot flame kernel initiates in fuel-rich region. Abstract: Gasoline compression ignition (GCI) engines favor low-octane fuels (RON = 60–80). However, low-octane fuels possessing low-temperature reactions strongly interact with in-cylinder thermodynamic conditions, which in turn significantly affect GCI combustion characteristics. In this work, using a toluene primary reference fuel (TPRF) with RON = 75, the effects of intake pressure and temperature on combustion evolutions, low-temperature heat release (LTHR), high-temperature heat release (HTHR), and indicated thermal efficiency were numerically investigated in a single-cylinder GCI engine, allowing for the role of octane sensitivity. An early injection timing was considered to obtain relatively homogeneous mixtures and large variations in intake pressure were employed to simulate low to medium loads. The results show that for a given equivalence ratio, the peak of the LTHR and HTHR and the main combustion phasing positively correlates with intake pressure. However, an opposite tendency in the peak of the HTHR is observed for a fixed amount of fuel injection. When octane sensitivity is elevated, the peak of in-cylinder pressure and heat release rate is reduced and ignition timing is retarded, especially for the HTHR. Elevating intake temperature facilitates high-temperature combustion while suppresses low-temperature reactions, which results in nonlinear variations in combustion phasing at a certain range of intake temperatures. The correlations of operating conditions and combustion evolutions are evaluated by pressure-temperature trajectory and Livengood-Wu integration, which indicates the significance of intake pressure in GCI combustion. Finally, combustion evolutions show that low-temperature reactions first take place at fuel-lean regions and hot flame pockets develop in fuel-rich regions, which suggests that low-temperature ignition is more sensitive to ambient temperatures while high-temperature ignition is more dependent on equivalence ratio.